Heroic Measures for an American Hero: Attempting to save the Life of General Douglas MacArthur. Issue 12 (December 2017) - Pappas, Theodore N.
General Douglas MacArthur was a towering public figure on an international stage for the first half of the 20th century. He was healthy throughout his life but developed a series of medical problems when he entered his 80s. This article reviews the General's medical care during two separate life-threatening medical crises that required surgical intervention. The first episode occurred in 1960 when MacArthur presented with renal failure due to an obstructed prostate. Four years later after his 84th birthday, MacArthur developed bile duct obstruction from common duct stones. He underwent an uncomplicated cholecystectomy and common duct exploration but developed variceal bleeding requiring an emergent splenorenal shunt. His terminal event was precipitated by strangulated bowel in long-ignored very large inguinal hernias. MacArthur died, despite state-of-the-art surgical intervention, due to renal failure and hepatic coma.